The Influence Of Pancasila And Local Wisdom On The Indonesian Character Development - Wiratih, Hernawati W. Retno; Rumyaru, Bruno; Aima, M. Havidz (Publika : Jurnal Administrasi Publik, 2021)
Culture is the bridge between health and psychology (mentality). Wisdom is a basis of integration of cognitive and affective that showed qualities of personality. A wise man lives their daily life in accord with wise perspectives and wise values. The local wisdom helps us to reach our wholeness by illuminating our inner world with the wisdom of our ancestors and helping us to discover our talents.Â  By the means of the values of Pancasila, the wholeness within the individual and the wholeness with nature and relations become the essential of character development, slow, and fast will create harmony. Â In community building, our life is enhanced. We can see how their lives are better because we are part of them. We have a place in their circle of life. We are constantly growing as a person.